PERAN PARTAI POLITIK DALAM PARTISIPASI DAN ASPIRASI POLITIK DI TINGKAT PEMERINTAHAN DESA (THE ROLE OF POLITICAL PARTIES IN PARTICIPATION AND POLITICAL ASPIRATION IN THE VILLAGE GOVERNMENT LEVEL) - Itok Wicaksono (POLITICO, 2017)
The results of the research indicate that community participation in the election of village heads in the three villages studied is always higher than the participation of the community in the other elections held in the village. The main reason for this is the familiar local figure and there is no denying the involvement of other parties who are often referred to as bebotoh in the Village Head Election. The results of this study also indicate that there is a large mass-based political party in each village (research location) but does not participate in the process of influencing influence on the title of Village Head Election. The political party is the National Awakening Party, almost never participating in the battle of Village Head Election in the village of Sruni, Kawang Rejo Village or in Selodakon Village.Keywords: Political Parties, Political Participation, Political Aspirations and Village Governance